Age-related, sport-specific adaptions of the shoulder girdle in elite adolescent tennis players - Cools, A. M.; Palmans, T.; Johansson, F. R. (Journal of Athletic Training, 2015)
Context: Tennis requires repetitive overhead movements that can lead to upper extremity injury. The scapula and the shoulder play a vital role in injury-free playing. Scapular dysfunction and glenohumeral changes in strength and range of motion (ROM) have been associated with shoulder injury in the overhead athlete.